Calculation of temperature distribution and rheological properties of the lithosphere along transect II in the Western Carpathian-Pannonian Basin region - DÉREROVÁ, Jana; BIELIK, Miroslav; PAŠIAKOVÁ, Mariana; KOHÚT, Igor; HLAVŇOVÁ, Petra (Contributions to Geophysics and Geodesy, 2014)
The temperature model of the lithosphere along transect II passing through the Western Carpathians and the Pannonian Basin has been calculated using 2D integrated geophysical modelling methodology. Based on the extrapolation of failure criteria, lithology and calculated temperature distribution, we derived the rheology model of the lithosphere in the area. Our results indicate a decrease of the lithospheric strength from the European platform and the Western Carpathians towards the Pannonian Basin. The largest strength can be observed within the upper crust which suggests rigid deformation in this part of the lithosphere. In the lithospheric mantle, strength almost disappears which allows us to assume that the ductile deformation dominates in this part of the lithosphere.